Media Portrayals of Hashtag Activism: a Framing Analysis of Canada's #Idlenomore Movement - Moscato, Derek (Media and Communication, 2016)
The confluence of activism and social media - legitimized by efforts such as the Arab Spring and Occupy Movements - represents a growing area of mainstream media focus. Using Canada’s #IdleNoMore movement as a case, this study uses framing theory to better understand how traditional media are representing activism borne of social media such as Twitter, and how such activism can ultimately have an impact in political and public policy debates. A qualitative framing analysis is used to identify frames present in media reporting of #IdleNoMore during its first two months by two prominent Canadian publications. Emergent frames show that hashtag activism as a catalyst for a social movement was embraced as a theme by one of the publications, therefore helping to legitimize the role of social media tools such as Twitter. In other frames, both positive and negative depictions of the social movement helped to identify for mainstream audiences both historical grievances and future challenges and opportunities for Canada’s First Nations communities. (author's abstract)